Response of bread wheat and nutrient removal with new micronutrient molecules fertilization - SINGH, ANAND; SHAHI, U P; DHYANI, B P; KUMAR, ASHOK; KUMAR, SATENDRA; VIVEK, VIVEK; KUMAR, ASHOK (The Indian Journal of Agricultural Sciences, 2021)
A field experiment entitled effect of newly formulated micronutrient fertilizers on crop performance, economic and nutrients uptake of wheat (Triticum aestivum L.) was conducted during rabi 2017-18 and 2018-19 at Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut, Uttar Pradesh, India. The recommended doses of N, P and K were applied @ 120 N: 60 P2O5: 40 K2O kg/ha in combination with different micronutrients fertilizers of Zn, Mn and B. The pooled data of experiment revealed that the growth and yield attributes including yield were maximum in T11 (RDF+ soil application of Zn HEDP + MnSO4+ Colemanite) while the cost of cultivation was minimum in T12. The study consisting of different combination of micronutrients sources indicated that highest values of growth parameters, yield attributes, grain yield (4.25 t/ha), straw yield (5.89 t/ha), net returns (54870 â‚¹/ha) and B:C ratio (2.12) were recorded with T11 (T1 +soil application of Zn HEDP + MnSO4+ Colemanite) followed by treatment T12 (T1 + foliar application of Zn HEDP + EDTA Mn + DOT). The uptake of zinc, manganese and boron was increased due to their application in combination with NPK either soil or foliar application. All the parameters including economics were minimum under T1. Appropriate combination of zinc, manganese and boron with recommended dose of primary nutrients for wheat crop was beneficial in every parameters including output.